Investigating mathematical proficiency testing in Namibian school high stakes mathematics examinations: an exploratory study - Ndjendja, Elizabeth (Rhodes University, Faculty of Education, Department of Education, 2019)
The Namibian government has put processes in place to continuously improve its education system in line with educational development in the world. The education reform efforts are administered and coordinated by the Ministry of Education, Arts and Culture. At the centre of these reform efforts are curriculum policy documents and subject syllabuses with the intention of improving the teaching and learning process in the classrooms. These reform efforts appears to overlook the positive influence high stakes assessment has on the teaching and learning process. The study reported in this thesis was designed to investigate the feasibility of assessing separate elements of mathematical proficiency in the high stakes Mathematics assessment in Namibia. The study was designed as a developmental, exploratory research that collected and analysed both qualitative and quantitative data in order to respond to issues raised by five specific research objectives. The data collected enabled the adaptation of some assessment tools in order to distinctly assess selected mathematical proficiency categories. The results further indicated that the envisaged proficiency assessment system could be used to characterise the examination question papers and revealed insights into the conceptualisation of the current assessment system. The results further indicated the visible distinguishability of different elements of proficiency through the developed tools and the learners' responses to the NSSCO examination. Finally, constrains and affordance which the original assessment system has in relation to the developed system were revealed and addressed. In closing, the research suggested changes and possible adaptation of assessment tools to ensure the proper assessment of mathematical proficiency aspects through high stakes assessment. Immerging issues that needed further research were also highlighted.
Keywords: Education and state -- Namibia; Educational tests and measurements -- Namibia; Mathematics -- Curricula -- Namibia; Mathematics -- Study and teaching -- Namibia; Namibia. Ministry of Education -- Examinations